The place of Croatian livestock production in European agriculture - Par, Vjekoslav; Njavro, Mario; Grgić, Ivo (Acta Agraria Kaposváriensis, 1999)
Livestock production is a very significant economic branch of Croatian agriculture, particularly the production of cattle and pigs. The recent years have been characterised by considerable changes in the structure of Croatian agricultural production. The importance of livestock production has decreased, such that in 1997 livestock production represented only 32.8% of the total value within the structure of Croatian agricultural production, while in 1992 it accounted for 44.4% of total agricultural production. The total number of cattle had decreased by 378,000 (45.6%) by 1997; i.e., from 829,000 in 1990 to 443,000. Trends in the num bers of other livestock species show situations which are not less unfavourable. According to official statistical data, in 1997 the total number of pigs was 1,176,000, 25.2% fewer than in 1990; that of sheep 453,000, 39.7% fewer; and that of poultry 10,954,000, 36.0% fewer. At the same time, in 1997 cattle production was 54,000 tonnes (1991: 76,000 tonnes), pig production 166,000 tonnes (1991: 185,000 tonnes) and poultry 85,000 tonnes (1991: 98,000 tonnes). Cow’s milk production in 1997 was 603 million litres (1991: 7 49 million litres) and hen’s egg production 804 million (1991:885 million). Livestock production on the family farms in Croatia dominated in 1997, and still has the significant role. The proportions accounted for by the family farms within the total number of livestock in 1997 were 88.7% for cattle, 74.7% for pigs, 96% for sheep and 60.8% for poultry, these figures remaining the same in 1998. According to the results of the analysis and comparison of the basic characteristics of livestock production in Croatia and in the EU-15 the average number of cows per farm in the EU-15 countries is. at approximately 20, more than 3.5 times that in Croatia. In milk production (milk being the most important product in the EU market) Croatian production is about 2300 litres per cow per year (on family farms about 3100 litres), while in EU-15 average annual milk production is about 5000 litres per cow. EU-151 attains 7,969,000 tonnes in cattle production annually, while in Croatia this was only 54,000 tonnes in 1997. EU-152 achieves 15,960,000 tonnes in pig production annually, Croatia only 85,697 tonnes in 1997.
Keywords: Livestock production; structure and index of production; family farms; EU-15